Hybrid Stem Cell States: Insights Into the Relationship Between Mammary Development and Breast Cancer Using Single-Cell Transcriptomics - Thong, Tasha; Wang, Yutong; Brooks, Michael D.; Lee, Christopher T.; Scott, Clayton; Balzano, Laura; Wicha, Max S.; Colacino, Justin A. (Frontiers in Cell and Developmental Biology, 2020)
Similarities between stem cells and cancer cells have implicated a role for mammary stem cells in breast carcinogenesis. Recent evidence suggests that normal breast stem cells exist in multiple phenotypic states: epithelial, mesenchymal, and hybrid epithelial/mesenchymal. The proportion of cells in these states vary between individuals, suggesting that state dynamics may be influenced by genetics or environment. Conditional reprogramming (CR), an in vitro method of expanding patient derived tissue samples, promotes the rapid induction of a stem-like state in the absence of genetic manipulation. The goal of this study was to use single-cell RNA sequencing to quantify the cell state distributions of normal human mammary (NM) cells isolated from patients undergoing voluntary reduction mammoplasty (n=3) before and after CR, investigating stem cell populations, and identifying gene and pathway drivers of stem cell phenotypes. Unbiased clustering revealed that post-CR, myoepithelial and luminal cell populations are retained, while fibroblast, endothelial, and immune cell populations are depleted. Compared to NM cells, CR cells show higher expression of an embryonic stem cell gene signature and differentially express stem cell and cancer related genes (LGALS1, SKA2, MKI67, HJURP, BIRC5, CCNB1, and BUB1). Pseudotime analysis and alignment to a mouse single-cell transcriptome atlas spanning mammary gland development revealed that NM cells align most closely to adult mouse cells and CR cells align across the trajectory with a population aligning to the embryonic mouse cells. We identified the emergence of three hybrid populations, a KRT14+/KRT18+ population (L/B), consistent with luminal progenitor cells, an EPCAM+/VIM+ (E/M) population, associated with cells undergoing the epithelial to mesenchymal transition, and a quadruple positive hybrid population, expressing all four markers. Pseudotime analysis and alignment to the mouse developmental trajectory revealed that E/M hybrids are the most developmentally immature, aligning along both luminal and basal developmental trajectories. Finally, pseudotime analysis and alignment of bulk breast tumors from the cancer genome atlas (TCGA), revealed that breast cancer subtypes express distinct developmental signatures, with basal tumors expressing the most “developmentally immature” phenotype. These results highlight phenotypic plasticity of normal mammary stem cells and provide insight into the relationship between hybrid cell populations, stemness, and cancer.